2010
DOI: 10.1002/cncr.25054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for recurrent breast cancer patients with an isolated, limited number of lung metastases and implications for pulmonary metastasectomy

Abstract: BACKGROUND:The aim of this study was to evaluate the clinical treatment outcomes of recurrent breast cancer with a limited number of isolated lung metastases, and to evaluate the role of pulmonary metastasectomy. METH-ODS: The authors consecutively enrolled 140 recurrent breast cancer patients with isolated lung metastasis from 1997 to 2007 in Seoul National University Hospital and retrospectively analyzed 45 patients who had <4 metastatic lesions. RESULTS: Fifteen patients had pulmonary metastasectomy followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
3
33
1
12
Order By: Relevance
“…The median survival period of pulmonary metastasis patients subsequent to systemic treatment remains approximately 24 months (19,20). Several studies have suggested that surgical treatment for operable lung metastases from breast cancer followed by systemic treatment prolongs survival to a greater extent compared to standard systemic treatment alone, in patients with <4 pulmonary metastases or with a DFI >3 years (21)(22)(23). The present study also suggests that pulmonary resection for solitary lung metastasis from breast cancer is likely to contribute to the improvement of prognosis, although a combined systemic therapy might be required.…”
Section: A B a Bsupporting
confidence: 52%
See 1 more Smart Citation
“…The median survival period of pulmonary metastasis patients subsequent to systemic treatment remains approximately 24 months (19,20). Several studies have suggested that surgical treatment for operable lung metastases from breast cancer followed by systemic treatment prolongs survival to a greater extent compared to standard systemic treatment alone, in patients with <4 pulmonary metastases or with a DFI >3 years (21)(22)(23). The present study also suggests that pulmonary resection for solitary lung metastasis from breast cancer is likely to contribute to the improvement of prognosis, although a combined systemic therapy might be required.…”
Section: A B a Bsupporting
confidence: 52%
“…Lung resection is a controversial treatment for pulmonary metastasis from breast cancer (5,(19)(20)(21)(22)(23). In this study, the five-year survival period for solitary lung metastasis from breast cancer patients was 100% after pulmonary resection.…”
Section: A B a Bmentioning
confidence: 85%
“…(21,22) evolution of patients with isolated pulmonary metastatic disease remains a concern. (12) Expression of Ki-67, a tumor marker closely related to the process of cell proliferation, might represent a negative prognostic factor. (24,25) The breast cancer subtypes in which there is high Ki-67 expression have been shown to respond better to the initial chemotherapy but have also been associated with a poor long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9) Such pulmonary metastases have been associated with a poor prognosis. (10,11) Because the lungs are common sites of metastatic disease, (12) the identification of malignant cells in the pleural fluid, together with the results of a biopsy of the parietal pleura, can provide evidence that the primary disease has spread or progressed, and such progression has been associated with decreased life expectancy. (13) Therefore, we stress the importance of identifying organ-specific characteristics of metastatic breast cancer, because such data can further the understanding of the natural history of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Pulmonary metastasectomy for metastatic breast cancer was begun more than two decades ago and, since then, few studies were performed which reported significant effects of metastasectomy in improving overall and long-term survival. [16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In a recent metaanalysis, the pooled overall five-year survival rate following pulmonary metastasectomy was found to be 46% in patients with breast cancer, while it was 22.5% following systemic treatment in patients with metastatic breast cancer. [34,35] In another study, Yhim et al [30] compared the results of pulmonary metastasectomy in 15 patients with metastatic breast cancer with 30 patients who received systemic treatment alone, and found significantly longer progression-free survival and overall survival in the metastasectomy group.…”
Section: Discussionmentioning
confidence: 99%